Ovarian histology and fecundity in the evaluation of the reproduction of the invasive species Serrasalmus marginatus (Characidae) on a neotropical floodplain (Acta Scientiarum. Biological Sciences, 2017)
The construction of the Itaipu Hydroelectric Power Plant in 1982 led to the formation of a reservoir, which, in turn, leveled the waters of the Paraná River by flooding the geographic barrier Salto de Sete Quedas. This allowed the piranha Serrasalmus marginatus to invade and colonize the upper Paraná River. This study aimed to: i) confirm, through light microscopy, the reproductive phases of S. marginatus females; ii) estimate fecundity and iii) evaluate the reproduction areas of the population. A total of 764 females were collected from nine sampling sites on the upper Paraná River floodplain. Microscopic analysis of the ovaries showed the following phases: early developing subphase, developing phase, spawning capable phase, actively spawning subphase, regressing phase and regenerating phase. The frequency distribution of the oocytes shows that spawning is fractional and fecundity indeterminate. Fecundity varied from 410 to 752 oocytes (mean = 584). The continual spawning of oocytes during the long reproductive period, as well as the aggressiveness of the species as regards the defense of its offspring, guarantees more descendants in the Patos, Ventura, Fechada, Guaraná and Garças lagoons and Ivinheima and Baia rivers of the upper Paraná River floodplain.